Abnormal white matter connections between medial frontal regions predict symptoms in patients with first episode schizophrenia. (October 2015) - Ohtani, Toshiyuki; Bouix, Sylvain; Lyall, Amanda E.; Hosokawa, Taiga; Saito, Yukiko; Melonakos, Eric; Westin, Carl-Fredrik; Seidman, Larry J.; Goldstein, Jill; Mesholam-Gately, Raquelle; Petryshen, Tracey; Wojcik, Joanne; et al.
Abstract: Introduction: The medial orbitofrontal cortex (mOFC) and rostral part of anterior cingulate cortex (rACC) have been suggested to be involved in the neural network of salience and emotional processing, and associated with specific clinical symptoms in schizophrenia. Considering the schizophrenia dysconnectivity hypothesis, the connectivity abnormalities between mOFC and rACC might be associated with clinical characteristics in first episode schizophrenia patients (FESZ). Methods: After parcellating mOFC into the anterior and posterior part, diffusion properties of the mOFC-rACC white matter connections for 21 patients with FESZ and 21 healthy controls (HCs) were examined using stochastic tractography, one of the most effective Diffusion Tensor Imaging (DTI) methods for examining tracts between adjacent gray matter (GM) regions. Results: Fractional anisotropy (FA) reductions were observed in bilateral posterior, but not anterior mOFC-rACC connections (left: p  < .0001; right: p  < .0001) in FESZ compared to HCs. In addition, reduced FA in the left posterior mOFC-rACC connection was associated with more severe anhedonia-asociality (rho = −.633, p  = .006) and total score (rho = −.520, p  = .032) in the Scale for the Assessment of Negative Symptoms (SANS); reduced FA in the right posterior mOFC-rACC connection was associated with more severe affective flattening (rho = −.644, p  = .005), total score (rho = −.535, p  = .027) in SANS, hallucinations (rho = −.551, p  = .018), delusions (rho = −.632, p  = .005) and total score (rho = −.721, p  = .001) in the Scale for the Assessment of Positive Symptoms (SAPS) in FESZ. Conclusions: The observed white matter abnormalities within the connections between mOFC and rACC might be associated with the psychopathology of the early stage of schizophrenia.